Exploring the Influence of Avian Vocal Presence on Appraisal of Urban Soundscapes - Mia Suhanek; Antonio Petosic; Ivan Djurek; Hans Slabbekoorn (Applied Sciences)
In this paper, six different acoustic environments with different loudness and sharpness levels were reproduced to two groups of listeners—control and experimental. The difference between the groups was achieved by adding different melodious singing bird sounds to the original recording of a children’s park. Therefore, the recording of the children’s park represents the recording listened to by the control group, while the experimental groups listened to the recordings of a children’s park mixed with different types of bird species. The questionnaire used in this research relies on the semantic differential method implemented by defining bipolar adjective pairs, which are selected in a way that they can significantly describe an auditory and emotional human response to a certain soundscape recording. In analyzing the results, psychological research methodology was used to determine the statistical significance of obtained human feedback, which enabled us to evaluate different acoustic environments appropriately. The calculation and correlation between the objective acoustic parameters (loudness, sharpness, roughness, and fluctuation strength) and subjective questionnaire parameters were carried out. The aim of this paper was to investigate the influence of different singing bird species, which are typical for Eastern Europe in terms of human appraisal and overall well-being, especially for participants residing in urban areas where the decline of biodiversity is already present. The results of this type of study could serve as a guideline for restoring and recovering biodiversity in urban areas across Europe; furthermore, it could benefit residents’ mood and overall health.